Dopamine D1 receptor involvement in latent inhibition and overshadowing - Nelson, Andrew J.D.; Thur, Karen E.; Cassaday, Helen J. (Cambridge University Press, 2012)
Latent inhibition (LI) manifests as poorer conditioning to a stimulus that has previously been experienced without consequence. There is good evidence of dopaminergic modulation of LI, as the eﬀect is reliably disrupted by the indirect dopamine (DA) agonist amphetamine. The disruptive eﬀects of amphetamine on LI are reversed by both typical and atypical antipsychotics, which on their own are able to facilitate LI. However, the contribution of diﬀerent DA receptors to these eﬀects is poorly understood. Amphetamine eﬀects on another stimulus selection procedure, overshadowing, have been suggested to be D1-mediated. Thus, in the current experiments, we systematically investigated the role of D1 receptors in LI. First, we tested the ability of the full D1 agonist SKF 81297 to abolish LI and compared the eﬀects of this drug on LI and overshadowing. Subsequently, we examined whether the D1 antagonist SCH 23390 can lead to the emergence of LI under conditions that do not produce the eﬀect in normal animals (weak pre-exposure). Finally, we tested the ability of SCH 23390 to block amphetamine-induced disruption of LI. We found little evidence that direct stimulation of D1 receptors abolishes LI (although there was some attenuation of LI at 0.4 mg/kg SKF 81297). Similarly, SCH 23390 failed to enhance LI. However, SCH 23390 did block amphetamine-induced disruption of LI. These data indicate that, while LI may be unaﬀected by selective manipulation of activity at D1 receptors, the eﬀects of amphetamine on LI are to some extent dependent on actions at D1 receptors.